Antiatherogenic Effect of Almond Oil in Streptozotocin Induced Diabetic Rats - Mona Anwara, Wafaa Ghoneim Shoushab, Hatem A. El-mezayenb, Raafat A wadallaha, Maha El-Wassefa, Naglaa M. Nazifc and Mona A. El-banaa (Journal of Applied Pharmaceutical Science, 2013)
The present study was conducted to evaluate the antiatherogenic effect of almond oil in diabetic rats. Forty five male white albino rats were divided into 3 groups: Control group, diabetic group and diabetic almond oil treated group. Experimental diabetes was induced by single subcutaneous injection of 50mg/kg body weight streptozotocin. After two months blood samples were collected, for assessment of triglycerides, total, HDL, and LDL cholesterol, insulin, intercellular adhesion molecule-1 (ICAM-1), nitrite and nitrate (NOx), hydrogen peroxide (H2O2), glutathione peroxidase activity (GPX) and DNA damage. Results showed that mean levels of cholesterol, triglyceride, LDL-cholesterol were significantly low and HDL-cholesterol was significantly high in diabetic group received almond oil compared to diabetic group. Mean concentrations of insulin, NOx, GPX activity were significantly high, and mean levels of H2O2, ICAM-1, percent of DNA damage were significantly low in diabetic group received almond oil compared to diabetic group. The data confirmed property of almond oil as an antioxidant that ameliorates oxidative stress and revealed that it is efficiently improves endothelial function and protects against the development of atherosclerosis in STZ induced diabetic rats.
Keywords: Diabetes, endothelial dysfunction, almond oil, atherosclerosis.